Analisis Indeks Pembangunan Manusia Pada 5 Wilayah Hasil Pemekaran Di Jawa Barat - Hariwan, Peggy; Swaningrum, Ayu (Jurnal Ekonomi Kuantitatif Terapan; 2015: Vol. 8, No. 1, Februari 2015 (pp. 1-112), 2015)
The purpose of this study is to examine the human development index of the five expansion regions in West Java such as Cimahi, Depok, Banjar, Bekasi and Tasikmalaya. The evaluation of the five cities is using data panel regression to the dependent variable of human development index. The study is tested with using data on 2003 to 2012. The findings of this study are GDP per capita and labor has a significant influence on Human Development Index. The policy of expansion region in 5 cities have already accomodated by indicators of Human Development Index which has increased due to the increasing in GDP per capita and the level of employment. This study is expected to develop some of  other variables for the expansion of regional policy in particularly for economic development.
Keywords: regional growth; human development index; the data panel